Integrated circuit failure analysis a guide to preparation techniques - Beck, Friedrich (Wiley series in quality and reliability engineering, 1998)
The construction and failure analysis of highly integrated semiconductor components has gained in significance with the explosive growth in the semiconductor industry. Once a subordinate laboratory task, semiconductor failure analysis has now become a discipline in its own right. The circuit designer must constantly expand the range of analytical and preparative methods, adapting them to the needs of new technologies in order to successfully locate faults and ensure optimum quality.